2018
DOI: 10.1177/1049732318804832
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Journeys of Recovery and Learning: A Participatory Arts-Based Inquiry

Abstract: The relationship between processes of mental health recovery and lifelong learning is an area of increasing international interest. Experiences of transformation, positive effects on self-esteem, self-insight, and empowerment have been identified regarding both endeavors. Recognition of these benefits has stimulated collaborative development of educational programs in personal development, self-efficacy, and recovery principles. The importance of evaluating this educational provision has been emphasized; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Relative to ethnicity, the March 3 to 15, 2021 CDC Household Pulse Survey reported that symptoms of anxiety or depression, over the past 7 days, were reported by 39.6% of Hispanic adults, 38.2% Black adults, and 35.9% of White adults. Relative to gender, in this same period, 40.5% of women and 33.1% of men reported symptoms of anxiety or depression (Centers for Disease Control and While most envision a health-related art intervention as the production of art (Bone, 2018;Casey & Webb, 2019;Van Lith, 2015), the term has also included exposure to arts and cultural activities, such as dance, drama, poetry, photography, film, and music (Chiang et al, 2019;Crone et al, 2018;Dunphy et al, 2019;Jensen et al, 2016;Poulos et al, 2019;van de Venter & Buller, 2015). Given this, art engagement can be either receptiveexposure to music, literature or theater-or active as in art-making (Vaartio-Rajalin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative to ethnicity, the March 3 to 15, 2021 CDC Household Pulse Survey reported that symptoms of anxiety or depression, over the past 7 days, were reported by 39.6% of Hispanic adults, 38.2% Black adults, and 35.9% of White adults. Relative to gender, in this same period, 40.5% of women and 33.1% of men reported symptoms of anxiety or depression (Centers for Disease Control and While most envision a health-related art intervention as the production of art (Bone, 2018;Casey & Webb, 2019;Van Lith, 2015), the term has also included exposure to arts and cultural activities, such as dance, drama, poetry, photography, film, and music (Chiang et al, 2019;Crone et al, 2018;Dunphy et al, 2019;Jensen et al, 2016;Poulos et al, 2019;van de Venter & Buller, 2015). Given this, art engagement can be either receptiveexposure to music, literature or theater-or active as in art-making (Vaartio-Rajalin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While most envision a health-related art intervention as the production of art (Bone, 2018; Casey & Webb, 2019; Van Lith, 2015), the term has also included exposure to arts and cultural activities, such as dance, drama, poetry, photography, film, and music (Chiang et al, 2019; Crone et al, 2018; Dunphy et al, 2019; Jensen et al, 2016; Poulos et al, 2019; van de Venter & Buller, 2015). Given this, art engagement can be either receptive—exposure to music, literature or theater—or active as in art-making (Vaartio-Rajalin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an emergent focus on recovery in mental health care (Happell, 2008;Casey and Webb, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an emergent focus on recovery in mental health care ( Happell, 2008 ; Casey and Webb, 2019 ). Recovery is not only focused on reducing symptoms, but also signals “a movement toward health and meaning rather than avoidance of symptoms” ( Clarke et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%